Pendidikan Intregrasi Di Pondok Pesantren Ulil Albab, Nganjuk - Wasito Wasito; Makhfud Makhfud (Indonesian Journal of Humanities and Social Sciences, 2020)
The development of the implementation of education in Indonesia towards the concept of integration in all fields of science. This practice was also carried out at the Ulil Albab Islamic Boarding School, Ngronggot Nganjuk. This study uses a qualitative method by interviewing all stakeholders in the Ulil Albab Islamic Boarding School. The results of this study indicate. First, integrated infrastructure. Second. Institutional integrity. Third, curriculum integration. Fourth, management integration. Fifth, the integration of traditions. While the target to be achieved is, "to be individuals who are good in body, good in mind, and kind in the heart (Healthy outer and inner), have a managerial system that is both solid and strong, has adequate educational facilities and varied unit institutions. While the efforts being made to achieve the target are; optimization of activities, optimization of management and supervision, institutional development, and development of infrastructure.